2016
DOI: 10.3390/risks4010004
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Frequency-Severity Regression Models in Insurance

Abstract: Abstract:In insurance and related industries including healthcare, it is common to have several outcome measures that the analyst wishes to understand using explanatory variables. For example, in automobile insurance, an accident may result in payments for damage to one's own vehicle, damage to another party's vehicle, or personal injury. It is also common to be interested in the frequency of accidents in addition to the severity of the claim amounts. This paper synthesizes and extends the literature on multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 58 publications
3
74
0
4
Order By: Relevance
“…Although, a series of recent studies shows that this unwarranted assumption can be relaxed in the collective risk model, and, thus, further in the Bayesian premium and BMS. In fact, the dependence between the frequency and severity in auto insurance is shown to be statistically significant in recent empirical studies such as Frees et al (2016) and Garrido et al (2016).…”
Section: Bms Based On Both Frequency and Severitymentioning
confidence: 98%
See 1 more Smart Citation
“…Although, a series of recent studies shows that this unwarranted assumption can be relaxed in the collective risk model, and, thus, further in the Bayesian premium and BMS. In fact, the dependence between the frequency and severity in auto insurance is shown to be statistically significant in recent empirical studies such as Frees et al (2016) and Garrido et al (2016).…”
Section: Bms Based On Both Frequency and Severitymentioning
confidence: 98%
“…However, a series of recent empirical studies have shown that the dependence between frequency and severity in auto insurance is statistically significant (Frees et al (2016); Garrido et al (2016)). This phenomenon invalidates the practice of using frequency-driven BMS and highlights the need to extend the classical collective risk model by allowing some dependence structure between frequency and severity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modeling individual claim amounts is equivalent to modeling the average severity only when N is included as a weight in the model forȲ . For more discussion, see Frees et al (2016).…”
Section: Definitions and Notationsmentioning
confidence: 98%
“…The proposed dependence model has some connections with aggregate claims models based on copulas (see for example Côté and Genest (2015)) and also with dependent GLM models (see Czado et al (2012)) or Frees et al (2016) and references therein. In addition, we incorporate a bivariate prior distribution which is conjugated with the likelihood of a claim being made.…”
Section: Introductionmentioning
confidence: 99%